Least Developed Countries and their progress on the sustainable development goals - Peter Lunenborg (South Centre, 2023)
This Research Paper reviews Least Developed Countries' (LDCs) collective progress on the implementation of the Sustainable Development Goals (SDGs), based on the available data on the indicators for the 169 SDG targets. It makes recommendations for LDCs and other States to consider advancing in relevant UN processes as well as the WTO's. LDCs made progress on 28% of the SDGs. This collective progress shows that these countries are far from achieving what were deemed achievable goals in 2015. With respect to trade-related SDGs, LDCs have not made progress on any of the five trade-related SDGs that mention LDCs specifically. This paper does not delve into the causes of this gap, but it suggests that international cooperation and, particularly, the developed countries' assistance, has been insufficient to address the needs of a large part of the world population that still lives in poverty and without hope of a better future. However, the Doha Programme of Action (DPoA), a development framework with targets specifically for LDCs - which overlap with SDG targets - appears to dilute several original SDG targets, in particular those in SDG 17 (Partnerships for the Goals).
Keywords: 300; Doha Programme of Action (DPoA); Global Indicator Framework; Least Developed Countries (LDCs); SDG Summit; Sustainable Development; Sustainable Development Goals (SDGs); Trade; Trade for Development; United Nations (UN); World Trade Organization (WTO)